On approach for homogeneity increasing of films grown from the gas phase with account natural convection and changes in the rate of chemical interaction between materials - Evgeny L. Pankratov (International Journal of Advances in Applied Sciences, 2019)
We analyzed growth of films by gas phase epitaxy. Based on the analysis we formulate conditions to increase of homogeneity of properties of obtained films. We also present an analytical approach for analysis processes framework gas phase epitaxy with account natural convection and the possibility of changing the rate of chemical interaction between reagents.